2022
DOI: 10.1007/s12975-022-01008-5
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Thrombectomy for Acute Basilar Artery Occlusion: Latest Findings and Critical Thinking on Future Study Design

Abstract: Randomized controlled trials (RCTs) have demonstrated powerful efficacy of endovascular thrombectomy (EVT) for large vessel occlusion in the anterior circulation. The effect of EVT for acute basilar artery occlusion (BAO) in the posterior circulation remains unproven. Here, we highlight the latest findings of observational studies and RCTs of EVT for BAO, with a focus on the predictors of functional outcomes, the limitations of recent RCTs, and critical thinking on future study design. Pooled data from large r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 63 publications
(136 reference statements)
1
16
0
1
Order By: Relevance
“…Despite a high frequency of ICAD, a subgroup analysis showed no treatment effect modification based on the presence of ICAD with a significant benefit in ICAD-related LVOs [ 19 ]. This is similar to prior studies that showed that, compared to patients without ICAD, patients with ICAD who received rescue treatment achieved similar rates of successful recanalization, favorable outcome, sICH, and mortality at 90 days [ 16 , 39 ].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Despite a high frequency of ICAD, a subgroup analysis showed no treatment effect modification based on the presence of ICAD with a significant benefit in ICAD-related LVOs [ 19 ]. This is similar to prior studies that showed that, compared to patients without ICAD, patients with ICAD who received rescue treatment achieved similar rates of successful recanalization, favorable outcome, sICH, and mortality at 90 days [ 16 , 39 ].…”
Section: Discussionsupporting
confidence: 89%
“…The generalizability of these findings need to be considered as three of the trials were completed in China and Asians are known to have high rates of ICAD [ 40 ]. However, as mentioned, prior studies showed that patients with ICAD who received rescue treatment achieved similar rates of successful recanalization and favorable outcome, compared to patients without ICAD [ 16 , 39 , 41 ]. Data on the percentage of ICAD were not available in the BAOCHE trial and we were unable to compare outcomes of patients with ICAD and without ICAD in this meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations